Reversed role of CD36 deficiency in high-fat diet or methionine/choline-deficient diet-induced hepatic steatosis and steatohepatitis - Zhu, Wenya; Ma, Jialing; Zhang, Tingting; Zhu, Mengmeng; Duan, Yajun; Yang, Xiaoxiao; Chen, Yuanli (Frontiers in Pharmacology, 2025)
IntroductionCluster of differentiation 36 (CD36) is highly expressed in the liver of patients with metabolic dysfunction-associated fatty liver disease (MAFLD) or metabolic dysfunction-associated steatohepatitis (MASH). However, the precise role of CD36 in MAFLD/MASH is controversial. In the current study, we aimed to uncover the role of CD36 in the early stage of MAFLD/MASH induced by high-fat diet (HFD) and methionine/choline-deficient (MCD) diet.MethodsCD36−/− mice and littermate control mice were fed a normal food diet (NCD); HFD or MCD diet for 6 weeks.ResultsWe determined that CD36 deficiency attenuated HFD-induced hepatic steatosis while exacerbating MCD diet-induced steatohepatitis. Mechanistically, CD36 deficiency reduced HFD-induced expression of fatty acid synthase (FASN), sterol regulatory element binding protein 1c (SREBP1c), and acetyl-CoA carboxylase alpha (ACC1), thereby inhibiting de novo fatty acid synthesis. The expression of superoxide dismutase and genes involving fatty acid oxidation was inhibited by MCD diet. CD36 deficiency reduced expression of genes involving fatty acid oxidation, while MCD diet had no effect on these genes expression in CD36−/− mice. Meanwhile, MCD diet-reduced superoxide dismutase expression was further inhibited by CD36 deficiency. Thus, MCD-induced liver ROS and inflammation were further enhanced by CD36 deficiency. By liver lipidomic analysis, we found that the levels of triglyceride (TG), diacylglycerols (DG), acylcarnitine (AcCA), ceramide (Cer) and LPC were increased, while phosphatidylcholine/phosphatidylethanolamine (PC/PE) were decreased in MCD diet-treated CD36−/− mice compared with MCD diet-treated wild type mice. Indeed, the expression of serine palmitoyltransferase 2 (SPTLC2), the key rate-limiting enzyme of ceramide synthesis, was higher in CD36−/− mice.DiscussionCD36 deficiency improves HFD-induced MAFLD by inhibiting fatty acid synthesis, while accelerating MCD diet-induced MASH via promoting Cer, LPC, TG and DG accumulation to accelerate liver inflammation. The complex role of CD36 in MAFLD/MASH needs more investigation to discover the precise and effective strategy when targeting CD36.